An Overview of Rhinoplasty Practices: European Academy of Facial Plastic Surgery, Collaborative Cross-Sectional Study - Mandavia, R; Parmar, D.; Ahmed, M.N.; Berber, V.; Sanz, D.; Paulucci, B.; D'Souza, A.R.; on behalf of the EAFPS Rhinoplasty Research Network (Facial Plastic Surgery, 2023)
This collaborative European Academy of Plastic Surgery (EAFPS) study aimed to provide an overview of rhinoplasty practices, informing clinician and patient decision making. It is a multicenter cross-sectional study, reported as per Strengthening the Reporting of Observational Studies in Epidemiology guidelines. All EAFPS members were contacted via email, inviting them to participate. Members expressing an interest to participate were asked to anonymously complete a questionnaire, related to rhinoplasties that they performed as first/supervising surgeon over a period from January 1, 2019 to January 1, 2022. A descriptive analysis was performed. One hundred and fifteen surgeons submitted data on 41,259 rhinoplasties from 33 countries. Eighty percent of rhinoplasties were primary, and 20% were secondary. Thirty five percent of primary rhinoplasties were closed and 65% were open. Thirty one percent of primary rhinoplasties were for cosmetic indications, 11% functional and 58% were for both. Of the 8147 secondary rhinoplasties, 44% were closed and 56% were open. Thirty percent were for cosmetic indications, 11% functional, and 59% for both cosmetic and functional. Ninety-one percent of rhinoplasties were performed by ENT surgeons, 3% by plastic surgeons, 5% by maxillofacial surgeons, and 1% were dual (maxillofacial and ENT) trained. One-thousand seven-hundred thirty primary rhinoplasties underwent revision surgery (5%) and 102 secondary rhinoplasties underwent revision surgery (1%). The most commonly reported indications for revision surgery were dorsal asymmetry, nasal blockage, and dissatisfaction with nasal tip. Three percent of rhinoplasties underwent preoperative psychological assessment. To the authors knowledge, this is the largest published rhinoplasty dataset. This study provides an overview of rhinoplasty practices that can be used for benchmarking and to guide clinician and patient decision making. Psychological assessment of prerhinoplasty appears insufficient with higher levels recommended to minimize unsuccessful outcomes. This study showcases the power of collaborative research and may serve as a catalyst for future collaborative facial plastic surgery research.
Keywords: rhinoplasty; cross-sectional; collaborative